Dark writing: Geography, performance, design - Carter, Paul (Honolulu University of Hawai, 2009)
We do not see empty figures and outlines; we do not move in straight lines. Everywhere we are surrounded by dapple; the geometry of our embodied lives is curviform, meandering, bi-pedal. Our personal worlds are timed, inter-positional, and contingent. But nowhere in the language of cartography and design do these ordinary experiences appear. This, Dark Writing argues, is a serious omission because they are designs on the world: architects and colonizers use their lines to construct the places where we will live. How can we explain the omission of bodies from maps and plans?